Neuropeptide Y receptor Y2 (npy2r) deficiency reduces anxiety and increases food intake in Japanese medaka (Oryzias latipes) - Lu, Ke; Jia, Xiaodan; Wu, Jiaqi; Wang, Qiuling; Liang, Xu-Fang (Frontiers in Cell and Developmental Biology, 2023)
Neuropeptide Y receptor Y2 (npy2r) is an important receptor gene involved in anxiety and feeding regulation in mammals. Since NPY receptors have different receptor gene deletions in mammals and teleost fish, it is not clear whether npy2r has the similar function in fish as in mammals. In this study, we used the CRISPR/Cas9 system to establish npy2r-deficient medaka (Oryzias latipes). Unexpectedly, the deletion of npy2r resulted in the npy2r+/- medaka were all-male, therefore, npy2r homozygous mutant lines could not be established. The deletion of npy2r increased the food intake in medaka, and the expression levels of appetite stimulating genes (agrp, npy) increased significantly, while the expression levels of anorexia factors (cck, pomc) decreased significantly. Moreover, the absence of npy2r significantly increased the total length and body weight of medaka. The mirror test and open field test showed that npy2r+/- medaka improved sociability and reduced anxiety-like behavior., qRT-PCR analysis showed that the expression levels of anxiety related genes (th1, th2, gr1, gr2, mr) in npy2r+/- medaka were significantly decreased. So far, this is the first npy2r gene knockout model established in fish and demonstrates that npy2r plays an important role in the regulation of reproduction, feeding and anxiety in fish.